Upgrade of the ALICE experiment: letter of intent - Abelev, Betty; Angelov, Venelin; Busch, Oliver; Glässel, Peter; Grajcarek, Robert; Herrmann, Norbert; Klein, Jochen; Kweon, MinJung; Lohner, Daniel; Lu, Xianguo; Maire, Antonin; Mercado Pérez, Jorge; et al. (Journal of physics. G, Nuclear and particle physics, 2014)
ALICE (A Large Ion Collider Experiment) is studying the physics of strongly interacting matter, and in particular the properties of the Quark-Gluon Plasma (QGP), using proton-proton, proton-nucleus and nucleus-nucleus collisions at the CERN LHC (Large Hadron Collider). The ALICE Collaboration is preparing a major upgrade of the experimental apparatus, planned for installation in the second long LHC shutdown in the years 2018-2019. These plans are presented in the ALICE Upgrade Letter of Intent, submitted to the LHCC (LHC experiments Committee) in September 2012. In order to fully exploit the physics reach of the LHC in this field, high-precision measurements of the heavy-flavour production, quarkonia, direct real and virtual photons, and jets are necessary. This will be achieved by an increase of the LHC Pb-Pb instant luminosity up to 6×1027 cm−2s−1 and running the ALICE detector with the continuous readout at the 50 kHz event rate. The physics performance accessible with the upgraded detector, together with the main detector modifications, are presented.
The ALICE collaboration: B. Abelev, V. Anguelov, O. Busch, P. Glässel, R. Grajcarek, N. Herrmann, J. Klein, M.J.Kweon, D. Lohner, X.-G. Lu, A. Maire, J. Mercado Perez, K. Oyama, Y. Pachmayer, K. Reygers, R. Schicker, J. Stachel, J.H. Stiller, S. Vallero, B. Windelband, A. Zimmermann [und weitere]
Gesehen am 23.09.2020